Students ‘Participation and Interest through Strategy Based Instruction in Reading Narrative Text - Lestariningsih, Enny Dwi; Dutta, Manashi Gogoi (Applied Research on English Education (AREE), 2024)
The development of digital technology currently affects all matters related to the learning and teaching process. Therefore, in the distance learning process, learning media, students’ participation, and interest are needed which are very necessary in responding to the challenges of today's education world. Therefore, this research aims to describe the students ‘participation and interest through strategy-based instruction in learning reading narrative text. The approach refers to students' understanding of how interested and understanding they are in studying English language material and how distributed to 27 students at one of the state universities in Indonesia. The results show that there is positive response from the students ‘participation and interest through strategy-based instruction. The most indicator is the students’ feeling happy and comfortable when learning using strategy-based instruction. Besides, it creates the teaching learners’ specific strategies to improve their skills and achieve their goals. Applying this concept to creating happiness can involve a variety of techniques and approaches such as; goal setting, positive thinking, mindfulness and meditation, healthy lifestyle, social connections, personal growth, time management, act of kindness, and self-care. Furthermore, the students' participation in strategy-based instruction involves actively engaging with the learning process, using specific strategies to enhance their understanding and performance. By actively involving students in the learning process and equipping them with effective strategies, educators can foster a more engaging and effective educational experience.Keywords: students ‘participation; students ‘interest; strategy based instruction; reading narrative text